Organic Electronics: Self‐Assembled Peptide–Polyfluorene Nanocomposites for Biodegradable Organic Electronics (Adv. Mater. Interfaces 14/2015). Issue 14 (September 2015) - Khanra, Soma; Cipriano, Thiago; Lam, Thomas; White, Tommi A.; Fileti, Eudes E.; Alves, Wendel A.; Guha, Suchismita
<x xml:space="preserve">Abstract</x> The functionalization of self‐assembled peptide nanostructures with blue‐emitting conjugated polymers of the polyfluorene family opens up a new generation of biodegradable materials in organic electronics. In article number 1500265, S. Guha and co‐workers demonstrate that the synthesis of diphenylalanine micro‐/nanostructures with polyfluorenes is mainly governed by van der Waals interactions. The nanocomposites show electroluminescence and are more than 80% biodegradable by enzymatic action.